Kerangka Hukum Kesetaraan Kerja dan Pengelolaan Keberagaman di Tempat Kerja - Rahmah Rafifah Abu; Rahmaniar Rahmaniar; Lince Bulutoding (Pusat Riset dan Inovasi Nasional, 2025)
Equal employment and diversity management are important issues in developing equitable human resources. This study aims to examine the legal framework related to Equal Employment Opportunity (EEO) and its application in creating an inclusive and discrimination-free work environment. The approach used is a literature study by collecting data from various literature, journals, and relevant regulations. The results of the study indicate that Indonesia has a fairly strong legal basis in guaranteeing equal employment opportunities, but challenges still arise in practice in the field such as discrimination based on gender, ethnicity, and other personal attributes. Effective diversity management requires an organization's commitment to implementing fair recruitment policies, inclusive training, and transparent assessment and compensation systems. From an Islamic perspective, the values ​​of justice, equality, and respect for human dignity are the moral basis that supports the implementation of EEO. Therefore, the integration of legal and ethical values, both from the state and religion, is very important in creating a healthy and sustainable work environment.